Manuscriptology and museology - Bobade, Bhujang Ramrao (New Delhi B. R. Publishing Corporation, 2017)
This is a new book in this filed which gives all details of Manuscriptology which is a important subject now a days for researchers. People thought that Manuscriptology is only for History and allied subjects but the real fact is that Manuscript is a basic and important document for all subjects such as Ayurveda, Siddha, Unani, Yogshastra etc.
Keywords: Museum techniques; Museology